PENGARUH LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN LQ45 2017 – 2021 - Laia, Soziduhu; Susanthi, Putu Rani (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
The purpose of this study was to determine the significance of the effect of leverage and firm size on profitability.This research is a causality study. The sample in this study was obtained by purposive sampling method. Data on the study population were 45 LQ45 index companies and 13 LQ45 index companies were obtained as samples with an observation period of four years (2017 - 2021). The data analysis technique used was multiple linear regression.The results of this analysis with multiple linear leverage have a positive and significant effect on profitability and firm size have a positive and significant effect on profitability. This study examines the influence of Leverage which is proxied by the Debt to Equity Ratio, Company Size which is proxied by Ln Total Assets and profitability which is measured by Return On Equity.Based on the results of testing the results show that F count is 0.809 with a significance of 0.042 a significance value which is less than 0.05, it can be said that leverage and company size simultaneously affect profitability in LQ45 companies listed on the Indonesia Stock Exchange in 2017 – 2021.